Effects of age, density and sex ratio on reproductive effort in male reindeer ( Rangifer tarandus) - Mysterud, Atle; Holand, Øystein; Røed, Knut H.; Gjøstein, Hallvard; Kumpula, Jouko; Nieminen, Mauri (Journal of Zoology, 2003)
Abstract In sexually dimorphic ungulates, male reproductive success depends on fighting with other males for access to females during a brief rutting season. Large body size is necessary for success in intrasexual competition, and a few large‐sized males are often able to monopolize access to female groups. Earlier studies have reported that reproductive effort increases with age until prime‐age is reached, and one study that population density lowered effort in (older) males. No study has directly assessed whether there is within‐age‐class variation in effort resulting from varying levels of intra‐male competition. It is reported here the weight loss during the rutting season of 54 individual male reindeer Rangifer tarandus coming from eight herds with varying density (3.3–6.0 deer/km 2 ) and sex ratio (4–28% males). In agreement with earlier studies, reproductive effort was lower for young (1‐ to 2‐year‐old) than for prime‐aged (3‐ to 5‐year‐old) males both on an absolute and relative scale. Among 1‐year‐old males ( n =33), effort was lower as sex ratio became closer to even, but density during the rutting season had no effect. This suggests that yearling males take a more active role when prime‐aged males are absent. In addition to the insight into male ungulate life history, understanding male rutting behaviour may also have implications for population dynamics.